Death at sea: certain factors responsible for occupational hazard in Polish seamen and deep-sea fishermen - Jaremin, B; Kotulak, E; Starnawska, M; Mroziński, W; Wojciechowski, E (International journal of occupational medicine and environmental health, 1997)
Deaths at sea, namely work-related fatal cases, are registered in all fleets throughout the world. Considering the medical and legal aspects, they are subject to notification, inquest, and possible indemnity. The aim of the study was to identify causes, circumstances, and mortality rates among Polish seamen and deep-see fishermen. The group studied comprised 113,260 employees of one shipping company and two fishing enterprises. Out of this number 148 fatal cases (109 seamen and 39 fishermen) registered during the years 1985-94 were investigated thoroughly. Mean annual rates of mortality (130.6) and fatal accidents (67.8) were calculated per 100,000 employees. They occurred to be higher than those among fishermen and the male population of the same age group (20-59 years) employed in various branches of the land economy, yet remaining lower compared to data on British and American seamen and fishermen. The risk of death was particularly high in persons above 40 years of age. It was demonstrated that unlike in the general population, 52% of deaths were due to external causes; primarily sea catastrophes, injuries, poisoning and missing. Among internal causes, circulatory diseases accounted for over 80% of deaths, including one fifth of cases due to acute myocardial infarction. In one third of these cases, cardiac failure had been already diagnosed before the voyage. The following circumstances were specific to deaths occurring during the voyage: deaths at open sea, frequently in the state of being alone in the cabin, no possibility of evacuating sick person to land medical institution, limited access to qualified medical assistance and effective rescue from outside, poor life-saving facilities and difficult communication. It was indicated that in a substantial percentage of fatal cases an adverse effect of the work performed, navigation and weather conditions proved to be hazardous, life-threatening and responsible for the fatal outcome. Sixty per cent of deaths were acknowledged by the shipowners as work-related or equivalent accidents with legal and economic consequences. The countermeasures proposed by the authors to minimize health hazards and life-threat at sea are of rather limited value for both organizational and economic reasons. The ship is still considered as one of the most dangerous workplaces.